The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1121/1.4845675
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tonotopicity, adaptation, modulation tuning, and temporal coherence in “primitive” auditory stream segregation

Abstract: The perceptual organization of two-tone sequences into auditory streams was investigated using a modeling framework consisting of an auditory pre-processing front end [Dau et al., J. Acoust. Soc. Am. 102, 2892-2905 (1997)] combined with a temporal coherence-analysis back end [Elhilali et al., Neuron 61, 317-329 (2009)]. Two experimental paradigms were considered: (i) Stream segregation as a function of tone repetition time (TRT) and frequency separation (Δf) and (ii) grouping of distant spectral components bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…Previous studies have shown that onset/offset asynchronies larger than 20-40 ms lead to increased stream segregation (e.g., Turgeon et al, 2002;Turgeon et al, 2005;Bregman and Pinker, 1978;Micheyl et al, 2013b;Christiansen et al, 2014), in good agreement with the data from this study.…”
Section: Resultssupporting
confidence: 88%
“…Previous studies have shown that onset/offset asynchronies larger than 20-40 ms lead to increased stream segregation (e.g., Turgeon et al, 2002;Turgeon et al, 2005;Bregman and Pinker, 1978;Micheyl et al, 2013b;Christiansen et al, 2014), in good agreement with the data from this study.…”
Section: Resultssupporting
confidence: 88%
“…As demonstrated by Ewert and Dau (2000), the processing of envelope fluctuations can be described effectively by a second-order bandpass filterbank with logarithmically scaled modulation filters. Such a processing has recently also been successful in speech intelligibility prediction studies (Jørgensen and Dau, 2011;Jørgensen et al, 2013), computational scene analysis (Christiansen et al, 2014), and sound textures synthesis (McDermott and Simoncelli, 2011). Similar processing based on auditory coding principles might also be advantageous in computational speech segregation, but this has not yet been examined.…”
Section: Introductionmentioning
confidence: 97%
“…Temporal coherence also explained why a few synchronous tone sequences perceptually pop-out even in the midst of a dense background of random tones4, and why prominent electroencephalogram responses to these synchronous tones emerge even in the absence of other distinguishing features such as global changes in signal power or local tone densities56. Finally, temporal coherence has also been demonstrated to play a role in co-modulation masking release78 and its dynamics have recently been imaged in the primary auditory cortex9.…”
mentioning
confidence: 94%